Developing effective listening skills for oral group discussions - Wan Jumani, Fauzi; Ezihaslinda, Ngah; Noor Raha, Mohd Radzuan; Amy Zulaikha, Mohd Ali; Noor Azlinda, Zainal Abidin; Hazlina, Abdullah (Kaizentrenovation Sdn Bhd, 2019)
In many higher education institutions (HEIs) around the world, group discussion is one of the popular English oral assessments for English as a Second Language (ESL) learners. It is usually conducted in a group of three or four students. For students to be competent in group discussions, they need to have the ability to manage topics in a discussion, which covers knowing how to initiate a topic, how to expand on the topic as well as seamlessly how to move from one topic to another. It also includes knowing how to introduce new topics to other speakers during the group discussion. This means for students to successfully participate in the group discussion, they are required to actively utilise their linguistic abilities and also their paralinguistic features. The challenge for language instructors is that the students have a tendency to focus more on their own contributions in the group discussions, rather than listening to what other speakers are saying to further develop the topic of discussion. As a result, students do not realise that effective listening is a skill that they are required to develop as they are more concerned with their language production, and thereby they usually focus more on their speaking skills. In reality, both listening and speaking skills are equally important to achieve mutual understanding between the participants of the group discussion. The objective of a group discussion is not only to observe and evaluate students’ ability to speak but to ensure that all members fully and actively participate in the discussion to come to a mutual agreement. If they are not effectively listening to each other, then the quality of the discussion would be subpar. This conceptual paper addresses the importance of developing effective listening skills among ESL learners. It highlights types of listening, listening processes, listening strategies and effective listening skills from existing literature to identify ways to assist ESL learners to be more alert to other speakers’ responses, and subsequently become more interactionally competent when participating in oral group discussions.